The role of immunity in insulin resistance in patients with polycystic ovary syndrome - Zhang, Qixuan; Yang, Zhe; Ou, Xiangyang; Zhang, Mengying; Qin, Xiangyu; Wu, Gengxiang (Frontiers in Endocrinology, 2025)
Polycystic ovary syndrome (PCOS) is a prevalent disorder of the endocrine system with significant clinical implications, often leading to health complications related to adipose tissue accumulation, including obesity, insulin resistance (IR), metabolic syndrome, and type 2 diabetes mellitus. While the precise pathogenesis of PCOS remains unclear, it is now recognized that genetic, endocrine, and metabolic dysregulations all contribute significantly to its onset. The immunopathogenesis of PCOS has not been extensively explored, but there is growing speculation that immune system abnormalities may play a pivotal role. This chronic inflammatory state is exacerbated by factors such as obesity and hyperinsulinemia. Therefore, this review aims to elucidate the interplay between IR in PCOS patients, the controlled immune response orchestrated by immune cells and immunomodulatory molecules, and their interactions with adipocytes, hyperandrogenemia, chronic inflammation, and metabolic homeostasis.